Utilização de objetos de aprendizagem para inclusão de alunos surdos no ensino médio integrado ao técnico - Costa, Lenin Mendes (2021)
From the application of public policies that deal with the process of social inclusion of Persons with Disabilities (PwD) in Brazil, Federal Education Institutions began to occupy a prominent role, especially in the educational field when laws began to require, in addition to inclusion in the Education, the reservation of vacancies in the federal education network. As a final result, these people's access to education enabled both their entry into school and their access to scientific knowledge and the world of work. However, the course of this school inclusion did not occur in a linear or complete way within the Federal Institutes (IF). For example, at the Federal Institute of Alagoas, Campus Marechal Deodoro (Ifal/MD), after a diagnostic research, the need to use adapted materials to assist the teacher in the teaching and learning process of deaf students enrolled in Professional and Technological Education became evident. (EPT). The lack of these materials represents a challenge to school inclusion and education, which needs to adapt to the needs of these deaf students. Given this finding, a research was developed whose main objective was to carry out a study aimed at the use of learning objects (adapted material) for deaf students in High School Integrated to Technical and as specific objectives: i) develop a digital booklet adapted in Libras on the National Water Resources Policy (Law nº. 9.433/1997); ii) point out the existing correlation between water resources policy and environmental policy; and iii) contribute to professional training in the areas of water resources and the environment. With this, an Educational Product was created that allowed these students to acquire scientific knowledge and, consequently, their permanence in school on equal terms with their listening peers. The methodological path of the diagnostic research was based on a qualitative approach, of the action-research type, elaborated through a questionnaire applied to the students of the Medium Level Integrated Technical Course in the Environment at Ifal/MD, with the objective of subsidizing the development of two different moments: (i) elaboration of the diagnostic research with two deaf students of the referred course; and (ii) construction and application of the Educational Product. The data collected showed that there are no records of materials adapted for these students, and that such materials are extremely important in their teaching process. It was also found that the educational institution, faced with an inclusive pedagogical practice, needs to adapt to the legislation and mobilize to reverse this situation in order to promote research, new pedagogical methods and techniques, in order to create educational products and strategies that meet the special educational needs of certain groups of students and that provide effective learning conditions. The analyzed data, in dialogue with the authors present in the theoretical foundation, served as the basis for the elaboration of the Educational Product aimed at these students, as a way to contribute to the improvement of the teaching and learning process. In conclusion, the final evaluation of the respondents showed that the adapted material developed in this research work met the proposed objectives, being able to allow access to the knowledge available in the aforementioned course.